1727a Is occupational noise exposure during pregnancy related to language acquisition of the child?. (24th April 2018) - Jungewelter, Soile; Taskinen, Helena; Jansson-Verkasalo, Eira; Lindbohm, Marja-Liisa; Remes, Jouko; Huotilainen, Minna; Sallmén, Markku
Abstract : Introduction: We examined the impact of noise exposure during pregnancy on the child's language acquisition at the age of one and two years. Methods: We conducted a cohort study among women working in the food industry, as kindergarten teachers, musicians, dental nurses and pharmacists with a new born child. At the age of one year the analyses included 408 mother-child pairs and at the age of two years 288. The mother filled the baseline questionnaire before the child was 12 months old, and the language acquisition questionnaire when the child was 12 months (Infant-Toddler Checklist, ITC) and 24 months (MacArthur Communicative Development Inventories, MCDI) old. An occupational hygienist assessed the noise exposure in three categories: no exposure, low exposure, moderate/high exposure. We analysed the data using linear regression. Results: At the age of one there were no statistically significant differences among the adjusted mean language acquisition ITC-scores of the children in different exposure categories. The adjusted scores among boys were 30.1 (95% CI: 28.3 to 31.8) for no exposure, 29.7 (27.4–32.0) for low noise, and 29.3 (26.7–31.9) for moderate/high exposure. Among girls these were 33.7 (31.9–35.5), 33.8 (31.3–36.4), and 33.6 (31.3–36.0), respectively. No associations were found in analyses of social communication, speech production and language comprehension. Noise exposure was associated with lower scores among kindergarten teachers. At the age of two mean MCDI-scores did not differ significantly between the noise exposure groups. The adjusted mean scores for expressive vocabulary among girls were 295 (95% CI: 254 to 336) for no exposure, 303 (243–362) for low exposure, and 269 (212–326) for moderate/high exposure. Among boys the scores were 200 (154–246), 178 (111–246), and 225 (153–298), respectively. Discussion: We found no clear association between noise exposure during pregnancy and language acquisition among one-year- or two-year-old children.